O DESEMPENHO DAS EMPRESAS DO GRANDE ABC DE 2001 A 2008 - Moretti, Sandro Pasquini (2011)
This study investigates empirically the performance of companies in the Grande ABC region increasingly industrialized and economically representative for the country. The seven cities that represent the region, Santo André, São Bernardo do Campo, São Caetano do Sul, Diadema, Mauá, Ribeirão Pires and Rio Grande da Serra, have in recent years economic growth considerably above the country's growth and development has stimulated the growth of the country. The empirical analysis uses panel data and examines the performance of firms in the seven cities that make up the Grande ABC during the years 2001 to 2008 using the multilevel methodology and three performance measures: ROA, ROE and OROA. The multilevel approach allowed the identification of key factors that are associated or not to performance of these companies and these effects are the year, the company itself, the sub sector, the sector and the city that the company is located. Among the tree performance measures used there was significant convergence, in addition the study identified that there is a significant effect on corporate performance associated with the year and the company itself, and show that the sectors, subsectors and the city that the company is do not have a significant effect associated with these firm performance.